Determinants of the VAT gap - part 2 - Hoza, Beata (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The purpose of the paper is to identify the determinants of the gap in Value Added Tax and to assess the measures already taken in order to seal this gap. A thorough understanding of the VAT gap mechanism will facilitate the implementation of appropriate measures to limit the scale of occurrence of tax offenses. Determinants of the VAT gap do not only embrace tax fraud and tax evasion, although these two factors are the most important and are sometimes even identified with the concept of VAT gap. (presented are in Part 1 of this article). The size of the gap is also affected by other factors such as methodological errors, cyclical factors, gray area, problems with financial liquidity and bankruptcy of taxpayers. Their importance and problems with estimation will be presented in this part of the article.